Optimization of Two-Step Acid-Catalyzed Hydrolysis of Oil Palm Empty Fruit Bunch for High Sugar Concentration in Hydrolysate - Dongxu Zhang; Yee Ling Ong; Zhi Li; Jin Chuan Wu (International Journal of Chemical Engineering)
Getting high sugar concentrations in lignocellulosic biomass hydrolysate with reasonable yields of sugars is commercially attractive but very challenging. Two-step acid-catalyzed hydrolysis of oil palm empty fruit bunch (EFB) was conducted to get high sugar concentrations in the hydrolysate. The biphasic kinetic model was used to guide the optimization of the first step dilute acid-catalyzed hydrolysis of EFB. A total sugar concentration of 83.0 g/L with a xylose concentration of 69.5 g/L and a xylose yield of 84.0% was experimentally achieved, which is in well agreement with the model predictions under optimal conditions (3% H2SO4 and 1.2% H3PO4, w/v, liquid to solid ratio 3 mL/g, 130°C, and 36 min). To further increase total sugar and xylose concentrations in hydrolysate, a second step hydrolysis was performed by adding fresh EFB to the hydrolysate at 130°C for 30 min, giving a total sugar concentration of 114.4 g/L with a xylose concentration of 93.5 g/L and a xylose yield of 56.5%. To the best of our knowledge, the total sugar and xylose concentrations are the highest among those ever reported for acid-catalyzed hydrolysis of lignocellulose.